1980
DOI: 10.1002/oms.1210150404
|View full text |Cite
|
Sign up to set email alerts
|

The fragmentations of substituted cinnamic acids after electron impact

Abstract: The fragmentations of a number of cinnamic acids substituted at the phenyl ring have been studied with the aid of 70eV mass spectra and mass analysed ion kinetic energy spectra. Evidence is presented that the formation of [GH,O,]+ ions occurs by intramolecular aromatic substitution reactions. A mechanism is proposed for the energetically favourable loss of the substituents from meta and para positions of the phenyl ring. The analytical use of intramolecular aromatic substitution reactions is briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 14 publications
5
13
0
Order By: Relevance
“…These data strongly suggested that the ortho -isomer underwent a facile chlorine radical elimination via cyclization similar to that reported by Ronayne et al [10]. In addition, Schaldach and Grützmacher reported that m - and p -chlorocinnamic acids were capable of undergoing the same chlorine elimination process as the ortho analog [8]. …”
Section: Introductionsupporting
confidence: 79%
See 4 more Smart Citations
“…These data strongly suggested that the ortho -isomer underwent a facile chlorine radical elimination via cyclization similar to that reported by Ronayne et al [10]. In addition, Schaldach and Grützmacher reported that m - and p -chlorocinnamic acids were capable of undergoing the same chlorine elimination process as the ortho analog [8]. …”
Section: Introductionsupporting
confidence: 79%
“…The cis-trans isomerization of double bonds has been shown to be a facile process upon electron ionization [18]. The carbonyl oxygen of the ester is now positioned to assist in the elimination of the halogen from the 2-position of the phenyl ring through the formation of a transitory 2-ethoxy-benzopyrylium intermediate [8]. This mechanism is consistent with the fact that skeletal rearrangements are often assisted by the presence of highly unsaturated groups [18].…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations